Is the New ACR-SPR Practice Guideline for Addition of Oblique Views of the Ribs to the Skeletal Survey for Child Abuse Justified? - Marine, Megan B.; Corea, Donald; Steenburg, Scott D.; Wanner, Matthew; Eckert, George J.; Jennings, S. Gregory; Karmazyn, Boaz (American journal of roentgenology (1976), 2014)
The purpose of our study was to determine whether adding oblique bilateral rib radiography to the skeletal survey for child abuse significantly increases detection of the number of rib fractures. We identified all patients under 2 years old who underwent a skeletal survey for suspected child abuse from January 2003 through July 2011 and who had at least one rib fracture. These patients were age-matched with control subjects without fractures. Two randomized radiographic series of the ribs were performed, one containing two views (anteroposterior and lateral) and another with four views (added right and left oblique). Three fellowship-trained radiologists (two in pediatrics and one in trauma) blinded to original reports independently evaluated the series using a Likert scale of 1 (no fracture) to 5 (definite fracture). We analyzed the following: sensitivity and specificity of the two-view series for detection of any rib fracture and for location (using the four-view series as the reference standard), interobserver variability, and confidence level. We identified 212 patients (106 with one or more fractures and 106 without). The sensitivity and specificity of the two-view series were 81% and 91%, respectively. Sensitivity and specificity for detection of posterior rib fractures were 74% and 92%, respectively. There was good agreement between observers for detection of rib fractures in both series (average kappa values of 0.70 and 0.78 for two-views and four-views, respectively). Confidence significantly increased for four-views. Adding bilateral oblique rib radiographs to the skeletal survey results in increased rib fracture detection and increased confidence of readers.